2019
DOI: 10.1029/2019pa003608
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Chemical Weathering Intensity in the Mekong River Basin Since the Last Glacial Maximum

Abstract: High-resolution clay mineralogy and major element geochemistry of Core SO18383-3 collected off the Mekong River mouth in the southern South China Sea have been investigated, aiming to reconstruct sediment provenance and chemical weathering intensity since the last glaciation. The chronology is based on foraminiferal accelerator mass spectrometry 14 C dates. Clay mineral analysis suggests that the Mekong River is a major sedimentary source for the studied area. The values of chemical index of alteration (CIA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 86 publications
1
19
0
11
Order By: Relevance
“…Generally, Si is concentrated in coarse‐grained fraction (e.g., quartz), and Al is concentrated in fine‐grained fraction (e.g., clayey minerals). Thus, the SiO 2 /Al 2 O 3 ratio is widely used to indicate the grain size (Jiwarungrueangkul et al., 2019). The Al 2 O 3 , K 2 O, TFe 2 O 3 , and MgO contents were negatively correlated with SiO 2 /Al 2 O 3 ratio (Figures 5a–5d), indicating these elements held by fine‐grained fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, Si is concentrated in coarse‐grained fraction (e.g., quartz), and Al is concentrated in fine‐grained fraction (e.g., clayey minerals). Thus, the SiO 2 /Al 2 O 3 ratio is widely used to indicate the grain size (Jiwarungrueangkul et al., 2019). The Al 2 O 3 , K 2 O, TFe 2 O 3 , and MgO contents were negatively correlated with SiO 2 /Al 2 O 3 ratio (Figures 5a–5d), indicating these elements held by fine‐grained fraction.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the interpretation on the paleoenvironment meaning of silicate chemical weathering degrees documented by marine sediments is still controversial (Colin et al., 2006; D. Hu et al., 2012; C. Huang et al., 2018; Jiwarungrueangkul et al., 2019; Liu et al., 2020; Wei et al., 2006). The reported studies have shown that the monsoon‐related precipitation and temperature exert a major impact on the silicate chemical weathering degree after the late Pleistocene, when tectonic activities may have little impact; thus, the chemical weathering intensity indicates the summer monsoon in the source regions (M. Cai et al., 2019; Colin et al., 2006; J. Huang et al., 2016; Jiwarungrueangkul et al., 2019). However, on the orbital and millennium scales, chemical weathering displays a complex response to the environmental changes in certain monsoon regions (Liu et al., 2020; Wan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CaO * in CIA is corrected by comparing the molar contents of CaO with Na 2 O, and the lower value is regarded as the CaO content in the silicate fraction (Singh et al, 2005;Liu et al, 2020). K 2 O is preferentially leached in aqueous fluids compared to the immobile Al 2 O 3 during the chemical weathering process (Nesbitt and Young, 1982); therefore, a lower K 2 O/Al 2 O 3 ratio could indicate increased chemical weathering related to strengthened monsoon rainfall, according to the basic principles of silicate weathering (Wei et al, 2004;Clift et al, 2014;Jiwarungrueangkul et al, 2019a). TiO 2 /CaO and Rb/Sr ratios were used to evaluate the variation of terrigenous sediment input related to erosion in this study (Jiwarungrueangkul et al, 2019b;Li et al, 2019).…”
Section: Weathering and Terrigenous Input Indicatorsmentioning
confidence: 99%
“…Because of the relatively constant source of Core K17 (Figure 7), provenance changes could not significantly influence weathering and terrigenous indicators. Sea level change played an important role in controlling terrigenous sediment input to the southern SCS before or during the early Holocene (Jiwarungrueangkul et al, 2019a) but is relatively constant with a weak fluctuation since ca. 7-8 ka on the Sunda Shelf, when the coastline reached a modern position (Steinke et al, 2003;Hanebuth et al, 2011).…”
Section: Weathering and Terrigenous Input Indicatorsmentioning
confidence: 99%
“…The southern South China Sea inputs huge weathering products of parent rocks from surrounding river basins in Southeast Asia under the strong influence of the East Asian monsoon and sea-level change, and this region becomes a valuable region for studying sediment source-to-sink and land-sea interactions (Hanebuth et al, 2002;Hanebuth et al, 2009;Hanebuth et al, 2011;Steinke et al, 2008;Huang et al, 2016) (Figure 1). Offshore from the Mekong River, clay mineralogy of Cores MD01-2393, MD97-2150 (Liu et al, 2004), and SO18383-3 (Jiwarungrueangkul et al, 2019b) and Sr-Nd isotopic compositions of Core MD01-2393 (Liu et al, 2005) were employed to indicate the Mekong River is the primary source of terrigenous sediments. Liu et al (2004) and Liu et al (2005) showed that strengthened chemical weathering corresponds to increased sediment discharge and weakened physical erosion during interglacial periods in the Mekong River basin, whereas weakened chemical weathering is associated with reduced sediment discharge and intensified physical erosion during glacial periods since 190 ka ago.…”
Section: Introductionmentioning
confidence: 99%